Peran Komunikasi Non Verbal Dalam Keputusan Pernikahan Dini Di Kecamatan Pamijahan Kabupaten Bogor - Titien Yusnita (JURNAL KAJIAN ISLAM MODERN, 2019)
The International Committee on Anal Matters defines a child as a person under the age of 18 and the Anal Protection Act 2002 makes it that parents are responsible for preventing marriage or early marriage. Early marriage or child marriage raises problems where the prospective bride and groom drop out of school. Early marriage is also at risk of causing problems both physically and psychologically. Bogor Regency occupies the highest ranking in West Java Province in cases of early marriage. The aim of this research is to find out the role of interpersonal communication in families in deciding early marriage. The research method uses descriptive qualitative methods through in-depth interviews and focus group discussions on early assessment actors. The results of the study show that non-verbal interpersonal communication plays a very important role in the family when deciding on early marriage. The role of parents as part of the communication system is very important where openness in family communication can resolve family disputes more quickly and wisely.